2006
DOI: 10.1002/app.23777
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties and transparency of injection‐molded polyacetal with branched and linear structure: Influence of crystalline morphology

Abstract: Branched and linear polyacetals prepared by cationic bulk polymerization were molded under high-injection rate and pressure, and the resultant 1-mm-thick specimens were investigated regarding the crystalline morphology, mechanical properties, and transparency. The branched polyacetal exhibited shear-induced transformation of crystalline morphology, namely, the spherulites, the elongated spherulites, and shish-kebab morphology parallel to the flow direction, with increasing shear viscosity. The degree of orient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…14 Meanwhile, the highly oriented shish-kebab structures along the melt flow direction can be observed in the shear layers, as shown in Figure 6(d,e), respectively. This is consistent with those occurring in literature, 28 which found the shish-kebab structures of POM sample prepared by conventional injection molding. In addition, some oriented structures can also be observed in the skin layers, as shown in Figure 6(a), which were different from the shishkebab structures in the shear layers.…”
Section: Effect Of Peo Incorporation On Crystalline Morphologysupporting
confidence: 93%
“…14 Meanwhile, the highly oriented shish-kebab structures along the melt flow direction can be observed in the shear layers, as shown in Figure 6(d,e), respectively. This is consistent with those occurring in literature, 28 which found the shish-kebab structures of POM sample prepared by conventional injection molding. In addition, some oriented structures can also be observed in the skin layers, as shown in Figure 6(a), which were different from the shishkebab structures in the shear layers.…”
Section: Effect Of Peo Incorporation On Crystalline Morphologysupporting
confidence: 93%
“…The reason why the polyacetal terpolymers have higher activation volume than the polyacetal copolymers is not clear at present. However, it is reported that the branched polyacetal polymers has good tensile strength properties and the modulus like the shih‐kebab morphology 12. Although the polyacetal terpolymers and the polyacetal copolymers in this work have the almost same mechanical properties and the morphology, it is likely that the short branched structures present in the polyacetal terpolymers, due to the EHGE unit as the comonomer component, may provide the high yielding strength35 to the polyacetal terpolymers in the creep process as the slow strain property.…”
Section: Resultsmentioning
confidence: 99%
“…The samples for the NMR measurement were purified by dissolution‐reprecipitation method by using HFIP as a solvent and methanol as a precipitant, respectively. The DOX content in the polyacetal copolymers and the DOX and EHGE contents in the polyacetal terpolymers were determined by 1 H‐NMR spectrometry according to the same methods reported previously 11–13. The signals of the CH 2 CH 2 O group assigned to the DOX unit and the CH 2 CH 2 CH 3 group assigned to the EHGE unit were detected in the spectrum of 1 H‐NMR, and the each unit content was calculated from the area of each characteristic peak.…”
Section: Methodsmentioning
confidence: 99%
“…A large number of studies on the single crystals, spherulites, and whiskers of POM have been reported in the past several decades; however, the shish-kebab morphology of POM, which is common in other polymers, has not been reported substantially. [25,26] Pennings first discovered the shish-kebab structure in a polyethylene (PE) solution in 1965; the structure was then intensively investigated in other polymers, compounds, and composites. [27][28][29][30][31][32][33][34][35] For decades, the shear or flow field has been confirmed to induce a shish-kebab morphology and enhance crystallization.…”
Section: Introductionmentioning
confidence: 99%